Neural Blockade Anaesthesia of the Mandibular Nerve and Its Terminal Branches: Rationale for Different Anaesthetic Techniques Including Their Advantages and Disadvantages - Jason Khoury; Grant Townsend (Anesthesiology Research and Practice)
Anaesthesia of structures innervated by the mandibular nerve is necessary to provide adequate pain control when performing dental and localised surgical procedures. To date, numerous techniques have been described and, although many of these methods are not used routinely, there are some situations where their application may be indicated. Patient factors as well as anatomical variability of the mandibular nerve and associated structures dictate that no one technique can be universally applied with a 100% success rate. This fact has led to a proliferation of alternative techniques that have appeared in the literature. This selective review of the literature provides a brief description of the different techniques available to the clinician as well as the underlying anatomy which is fundamental to successfully anaesthetising the mandibular nerve.